Risk Factors, Dietary and Clinical Profile of Patients with Non-alcoholic Steatohepatitis (NASH): Across-sectional Study - Kumar, Vinod; Bhagat, Ritu; Azad, Ahmar Javid (Highlights on Medicine and Medical Science Vol. 3, 2021)
Introduction: Ludwig et al. coined the name NASH. Non-alcoholic steatohepatitis (NASH) is a type of non-alcoholic steatohepatitis that includes steatosis, steatohepatitis, fibrosis, cirrhosis and complications. Aim: The goal is to investigate the dietary, clinical, and other risk factors associated to NASH. Materials and Method: The current study was conducted in 2010 at the Department of Medicine, GMC, Jammu, on 60 NASH patients during a six-month period.All NASH patients were examined for a variety of NASH-related risk factors. A complete clinical examination and a detailed history were recorded. Results: Out of 60 patients, 28(46.66%) were males and 32(53.32%) were females. 85% of the patients were in the age group of 31-70 years. Conclusion: In our study, non-vegetarians accounted for 73.33% (44/60) of patients, while asymptomatic individuals accounted for 26.6% (16/60). The most common symptom was right subcostal pain (69.33%). This study showed that obesity, hyperlipidemia and diabetes mellitus were significantly associated with the NASH.